Pluchea indica extracts stimulates insulin secretion through enhancement of Irs2 and Glut2 genes expression in RIN-5F pancreatic β-cells - Arief Ichwan, Solachuddin Jauhari; Suriyah, Wastuti Hidayati; Kasmuri, Abdul Razak; Taher, Muhammad (2014)

(untitled)
Diabetes mellitus (DM) is a chronic metabolic disorder that has reached epidemic proportions with the estimated prevalence rates and trends are escalating largely in developing countries. The awareness of the modern drugs to treat DM which have numerous side effects has led to a recent growing interest in the therapeutic use of natural products, especially those derived from plants. Pluchea indica is abundantly distributed in Malaysia and it is traditionally claimed to have antidiabetic properties. Our previous in vivo study demonstrated that P. indica prevents hyperglycemia in streptozotocin-induced diabetic rats and reduce blood glucose in normal rats. Here we report for the first time the antidiabetic potential of P. indica in the insulin regulation through cell-based in vitro model by using RIN-5F pancreatic β-cells. P. indica was extracted from the powdered dry leaves using soxhlet apparatus with n-hexane, dichloromethane, ethyl acetate and methanol consecutively. The plant also was macerated using water to yield water extract. The maximum tolerable concentration of extracts on RIN-5F pancreatic β-cells was determined by MTT assay. The concentration of 0.2 mg/mL was found to be the maximum concentration of P. indica extracts in the absence of cytotoxicity. The insulin released was measured by a rat insulin enzyme-linked immunoassay (ELISA) system. We found that hexane and water extracts at concentration of 0.05 mg/mL and 0.1 mg/mL respectively stimulated insulin release (p<0.05). Moreover, the insulin stimulation was associated with elevated expression of Insulin receptor substrate 2 (Irs2) and glucose-transporter Glut2 genes as determined by Quantitative Reverse Transcription PCR (qRT-PCR). Taken together, these findings indicate dual positive action of P. indica as a candidate anti-diabetic drug from natural sources by stimulating insulin secretion in β-cells. These findings provide the following insights for future research in exploring the potential clinical usefulness of P. indica for diabetes management.